Changes in mechanical power output in rowing by varying stroke rate and gearing - Held, S.; Siebert, T.; Donath, L. (European Journal of Sport Science, 2020)
Each stretch-shortening-cycle (SSC) in elite sports (e.g. jumping, cycling), is characterised by utilising optimal movement-parameters (e.g. muscle shortening velocity), for maximum power (jump height, cycle velocity). It is however unclear if relevant SSC movement-parameters in rowing, such as stroke rate and gearing, have to be maximised to obtain maximum power output or if an optimum relation emerges. Thus, we measured rowing-power (Prow), leg-power (Pleg) and work-per-stroke (WPS) at of varying stroke rates (20-45 spm), gearings (lever-changes 0.87-0.90 m) and drag factors (100-180 Ws3/m3) during rowing. Experienced sub-elite young athletes performed sprint-series on (single scull, n = 69, 20 ± 2 years, 186 ± 7 cm, 84 ± 9 kg) and off the water (rowing-ergometer, n = 30, 19 ± 3 years, 185 ± 11 cm, 77 ± 19 kg). Prow increased with stroke rate for ergometer-test (r = 0.97, p < 0.001) and boat measurement (r = 0.98, p < 0.001) by 2.7%/stroke and 4.4%/stroke, respectively. Interestingly, stroke rate had a high impact on WPS (r = 0.79, p < 0.001) during boat measurement, compared to no (or specifically no high) impact on WPS (r = -0.10, p = 0.166) during ergometer-measurements. Drag factor (ergometer: r = 0.83, p < 0.001) and gearing (boat: r = 0.60, p < 0.001) yielded moderate to high correlations to Prow. These results indicate that no optimum stroke rate, gearing and drag factor exist for maximum power in rowing (sprint-measurement-range). Accordingly, the measurements yielded maximum power for maximum stroke rate, gearing, and drag factor.